Bioassays to screen the toxicity in drinking water samples collected in Brazilian rural area. Issue 4 (27th July 2021) - Brucker, Natália; Menezes, Charlene; Charão, Mariele Feiffer; da Silva, Laura Cé; Sant'anna Oliveira, Talitha Stella; Menezes, Júlia M; Muller, Isadora; Gioda, Adriana; de Carvalho, Bruna Rafaela Fretag; de Castro Paz Calheiros, Octávio; Rizzetti, Tiele Medianeira; Zanella, Renato; et al.
Abstract: Agriculture activities have increased the concentration of pesticides and metals in the environment. The excessive use of pesticides can generate an environmental impact and contribute to the development of human diseases. This study aimed to determine the presence of pesticides and metals in water samples collected in the Brazilian rural area in two different periods (before and after pesticide application) and to evaluate the alternative bioassays Lactuca sativa, Allium cepa, and Caenorhabditis elegans to monitoring toxicity in human drinking water samples. Eight sites in the rural area were selected and water samples were collected in two different periods of the year (before and after pesticide application). The presence of the pesticides was determinated by ultra-high performance liquid chromatography–tandem mass spectrometry and metals by inductively coupled plasma mass spectrometry. The potential toxicity of the water samples was performed with three different alternatives in vivo models ( L. sativa, A. cepa, and C. elegans ). Fifty-seven pesticides were analyzed and, according to the results, the most found ones were clomazone, atrazine, tebuconazole, metconazole, pyrimethanil, and carbofuran-3-hydroxide, which is a metabolic degradation product of insecticide carbofuran. The most detected metals were Cu, Cr, Mg, Fe, and Mn. The assays with L. sativa and A. cepa showed alterations in the period after pesticide application, while C. elegans presented changes in both periods compared to the same collection sites. These results indicate that bioassays, especially C. elegans, could be complementary and useful tools for monitoring the toxicity in drinking water samples.